Implementation of Inclusive Education at Sangkulirang Elementary School 006 East Kutai - Fathinnaufal, Martsel; Pamungkas, Bayu (FKIP - Universitas Riau, 2025)
The purpose of this study is to describe physical and non-physical accessibility in implementing inclusive education at SDN 006 Sangkulirang. The qualitative research approach with qualitative descriptive type, with eight informants, using instruments through interview guides. Data collection using interview techniques, observation and documentation. Interviews are the primary technique in data collection. Data analysis uses an interactive analysis model by Miles and Huberman through data presentation, condensation and conclusion drawing. The results of the study found that inclusive education on physical and non-physical accessibility at SDN 006 Sangkulirang is still inadequate, both in facilities and infrastructure, access to inclusive classrooms is not yet fully available, the physical environment of the school is not fully friendly for all students. These limitations can hinder the active participation and independence of children in participating in teaching and learning activities at school. While non-physical accessibility, teachers have shown good initiatives through the implementation of differentiated learning and the use of audio-visual media. These efforts help students with special needs in understanding the subject matter, and still need to be improved with the role of teachers in the practice of inclusive education.